Tubulin Cytoskeleton Organization in Cells of Determinate Nodules - Kitaeva, Anna B.; Gorshkov, Artemii P.; Kusakin, Pyotr G.; Sadovskaya, Alexandra R.; Tsyganova, Anna V.; Tsyganov, Viktor E. (Frontiers in Plant Science, 2022)
Plant cell differentiation is based on rearrangements of the tubulin cytoskeleton; this is also true for symbiotic nodules. Nevertheless, although for indeterminate nodules (with a long-lasting meristem) the organization of microtubules during nodule development has been studied for various species, for determinate ones (with limited meristem activity) such studies are rare. Here, we investigated bacteroid morphology and dynamics of the tubulin cytoskeleton in determinate nodules of four legume species: Glycine max, Glycine soja, Phaseolus vulgaris, and Lotus japonicus. The most pronounced differentiation of bacteroids was observed in G. soja nodules. In meristematic cells in incipient nodules of all analyzed species, the organization of both cortical and endoplasmic microtubules was similar to that described for meristematic cells of indeterminate nodules. In young, infected cells in developing nodules of all four species, cortical microtubules formed irregular patterns (microtubules were criss-crossed) and endoplasmic ones were associated with infection threads and infection droplets. Surprisingly, in uninfected cells the patterns of cortical microtubules differed in nodules of G. max and G. soja on the one hand, and P. vulgaris and L. japonicus on the other. The first two species exhibited irregular patterns, while the remaining two exhibited regular ones (microtubules were oriented transversely to the longitudinal axis of cell) that are typical for uninfected cells of indeterminate nodules. In contrast to indeterminate nodules, in mature determinate nodules of all four studied species, cortical microtubules formed a regular pattern in infected cells. Thus, our analysis revealed common patterns of tubulin cytoskeleton in the determinate nodules of four legume species, and species-specific differences were associated with the organization of cortical microtubules in uninfected cells. When compared with indeterminate nodules, the most pronounced differences were associated with the organization of cortical microtubules in nitrogen-fixing infected cells. The revealed differences indicated a possible transition during evolution of infected cells from anisotropic growth in determinate nodules to isodiametric growth in indeterminate nodules. It can be assumed that this transition provided an evolutionary advantage to those legume species with indeterminate nodules, enabling them to host symbiosomes in their infected cells more efficiently.